Concerns, quality of life, access to care and productivity of the general population during the first 8 weeks of the coronavirus lockdown in Belgium and the Netherlands - Hanne van Ballegooijen; Lucas Goossens; Ralph H. Bruin; Renée Michels; Marieke Krol (BMC, 2021)
Abstract Background The COVID-19 pandemic has a disruptive impact on our society. We therefore conducted a population survey to describe: 1) stress, concerns and quality of life 2) access to healthcare and cancelled/delayed healthcare and 3) productivity during the first 8 weeks of the coronavirus lockdown in the general population. Methods An online cross-sectional survey was conducted in a representative sample after 8 weeks of the coronavirus lockdown in Belgium and the Netherlands. The survey included a series of three validated questionnaires about quality of life delayed/cancelled medical care and productivity loss using validated questionnaires. Results In total, 2099 Belgian and 2058 Dutch respondents completed the survey with a mean age of 46.4 and 42.0 years, respectively. Half of the respondents were female in both countries. A small proportion tested positive for COVID-19, 1.4% vs 4.7%, respectively. The majority of respondents with a medical condition was worried about their current health state due to the pandemic (53%) vs (63%), respectively. Respondents experienced postponed/cancelled care (26%) and were concerned about the availability of medication (32%) for both countries. Productivity losses due to the COVID-19 restrictions were calculated in absenteeism (36%) and presenteeism (30%) for Belgium, and (19%) and (35%) for the Netherlands. Most concerns and productivity losses were reported by respondents with children < 12 years, respondents aged 18-35 and respondents with an (expected) COVID-19 infection. Conclusions This study describes stress, quality of life, medical resource loss and productivity losses in Belgium and the Netherlands after 8 weeks of coronavirus lockdown. The results underline the burden on society.